Visual imaging as a predictor of neurodegeneration in experimental autoimmune demyelination and multiple sclerosis - Gabrielle M. Mey; Kirsten S. Evonuk; McKenzie K. Chappell; Laura M. Wolfe; Rupesh Singh; Julia C. Batoki; Minzhong Yu; Neal S. Peachey; Bela Anand-Apte; Robert Bermel; Daniel Ontaneda; Kunio Nakamura; et al. (Acta Neuropathologica Communications, 2022)
Abstract Thalamic volume is associated with clinical disability in multiple sclerosis (MS) and is vulnerable to secondary neurodegeneration due to its extensive connectivity throughout the central nervous system (CNS). Using a model of autoimmune demyelination that exhibits CNS-infiltrating immune cells in both spinal cord white matter and optic nerve, we sought to evaluate neurodegenerative changes due to lesions affecting the spino- and retino-thalamic pathways. We found comparable axonal loss in spinal cord white matter and optic nerve during the acute phase of disease consistent with synaptic loss, but not neuronal cell body loss in the thalamic nuclei that receive input from these discrete pathways. Loss of spinal cord neurons or retinal ganglion cells retrograde to their respective axons was not observed until the chronic phase of disease, where optical coherence tomography (OCT) documented reduced inner retinal thickness. In patients with relapsing–remitting MS without a history of optic neuritis, OCT measures of inner retinal volume correlated with retino-thalamic (lateral geniculate nucleus) and spino-thalamic (ventral posterior nucleus) volume as well as neuroperformance measures. These data suggest retinal imaging may serve as an important noninvasive predictor of neurodegeneration in MS.